A novel "AIE + ESIPT" near-infrared nanoprobe for the imaging of γ-glutamyl transpeptidase in living cells and the application in precision medicine. Issue 17 (24th July 2019) - Liu, Yi; Feng, Bin; Cao, Xiaozheng; Tang, Gao; Liu, Honglu; Chen, Fang; Liu, Meihui; Chen, Qian; Yuan, Kai; Gu, Yonghong; Feng, Xueping; Zeng, Wenbin
Abstract : Novel near-infrared nanoprobe for detecting GGT in HepG2 cells and imaging in liver tumour tissue, satisfying for the need for clinical measure of GGT level. Abstract : γ-Glutamyl transpeptidase (GGT) has been reported as a biomarker of hepatocellular carcinoma (HCC), and its imaging is of great benefit for early detection in precise medicine as well as intraoperative navigation. Herein, we have designed and synthesized a novel near-infrared fluorescent probe coupled aggregation-induced emission (AIE) and excited-state intramolecular proton transfer (ESIPT) effect for the detection of GGT. Thanks to conjugated glutamate acid, this probe could be dispersed in aqueous solution and showed barely any fluorescence emission. Through a GGT-mediated enzymatic reaction, the aggregation state of the probe in aqueous solution was changed and an intramolecular hydrogen bond was formed, resulting in an enhanced fluorescence emission. An excellent linear relationship was observed and the concentration of GGT measured was in the range of 10–90 U L −1 with a limit of detection calculated at 2.9 U L −1 . Its feasibility has been confirmed by detecting GGT in HepG2 cells with high specificity and long-term sustainability, satisfying clinical need. Moreover, this nanoprobe showed great potential for precise medicine guided surgery by realizing fluorescence imaging in human liver tumour tissue and distinguishing it from normal tissue. Thus, we supposed that our AIE coupled ESIPT fluorescent nanoprobe has great potential in the early detection of HCC, the selective fluorescence imaging of GGT positive cells during surgery and application in precision medicine.